The effect of Chaihu-shugan-san on cytotoxicity induction and PDGF gene expression in cervical cancer cell line HeLa in the presence of paclitaxel +cisplatin - Jianfang, Xue; Ling, Zhu; Yanan, Jiao; Yanliang, Guan (Cellular and Molecular Biology, 2021)
Chaihu-shugan-san, as a traditional Chinese herbal formula, is composed of seven different herbs. This medicine can treat cancer due to its antioxidant compounds. In this study, the effect of Chaihu-shugan-san was considered on cytotoxicity induction and PDGF gene expression in cervical cancer cell line HeLa at different concentrations and at different times, by the MTT method. Paclitaxel + cisplatin were used as a control in this study. The expression of the PDGF gene was quantitatively evaluated in treated cells by real-time PCR, and a generalized linear model was used to evaluate the effect of the medicine, and Duncan's multiple range tests were used to evaluate the data. The results of the MTT test showed that Chaihu-shugan-san had antitumor properties in different concentrations, but there was a significant difference between this medicine and paclitaxel +cisplatin. Also, examination of gene expression showed that this medicine reduced the expression of the PDGF gene in the HeLa cancer cell line (P ? 0.04). Therefore, Chaihu-shugan-san could be suggested as an effective factor in preventing the growth of cervical cancer cells and controlling angiogenic factors that play an important role in the metastasis of cancerous tumors.